Pendidikan Tradisi Makan Menggunakan Talam Di Pesantren Gerentam (Kajian Living Hadis) - Wasila Sukardin (An-Nadwah, 2024)
The tradition of eating using a Talam is a practice adopted in the Isra Miraj celebration at the Gerentam Islamic Boarding School, an important ritual for Muslims. Uniquely, in this practice, food is served in a tray occupied by ten people, reflecting the uniqueness of this tradition. The origins and understanding of the practice of eating using a Talam is interesting to research, considering that this practice has been going on since the time of the ulama around the Islamic boarding school and has been preserved until now. This research aims to explore the origins and meaning of the practice of eating using Talam. The research method used is field research with a qualitative descriptive approach. Primary data was collected through interviews with sources, direct observation, documentation, and secondary data. This research was conducted at the Gerentam Islamic Boarding School, South Sumatra. The history of the practice of eating using a Talam begins with Islamic boarding school leaders and ulama who gained experience and knowledge from the land of Java, then conveyed this practice through lectures at recitation events, which are traditionally held every year in the month of Rajab. The research results show that this practice has been going on for the last 40 years. More than just a ritual tradition, the practice of eating using a Talam contains the meaning and values of worship, such as maintaining relationships, appreciating sufficiency, and hoping to receive blessings. In this practice, there is a deep meaning which is based on the hadith of the Prophet, which is the basis for the implementation of eating using a Talam at the Gerentam Islamic Boarding School. Apart from that, this practice also reflects religious values in accordance with the teachings of the Prophet Muhammad SAW.